The Effect of Model Assisted By Zep Quiz on Studens' Learning Outcome - Thahirah, Azizah; Oktavia, Rani; Azhar, Aulia (Pendidikan IPA, FMIPA, UNP, 2026)
This research explores the problem of low academic performance in science among students at SMP Negeri 2 Payakumbuh. To address this challenge, the application of a suitable learning model is deemed crucial. The Student Teams Achievement Division, a model of collaborative education, along with the incorporation of Zep Quiz technology, is proposed as a potential approach to improve students' comprehension of the topic Elements, Compounds, and Mixtures. The study utilized a quasi-experimental design with a non-equivalent control group format. The participants were eighth-grade students from the 2024/2025 school year, class VIII.9 was designated as the experimental group, while class VIII.8 served as the control group, selected through purposive sampling. The class that participated in the experiment was taught with the STAD approach, aided by Zep Quiz, whereas the control class utilized traditional teaching practices. To gather data, pre-tests and post-tests were administered, followed by analysis of the data for normality, homogeneity, and hypothesis testing, which was performed using Microsoft Excel. The results of the t-test indicate a significant distinction between the experimental and control groups (tcount = 2.83 > ttable = 2.00). These results suggest that applying the STAD cooperative model, aided by Zep Quiz media, significantly enhances students’ learning outcomes in science. The model encourages collaborative learning, active student involvement, and interactive digital-based formative assessments, leading to a more effective and engaging learning experience.